Aromatic acids as biomass-burning tracers in atmospheric aerosols and ice cores: A review. (April 2019) - Wan, Xin; Kawamura, Kimitaka; Ram, Kirpa; Kang, Shichang; Loewen, Mark; Gao, Shaopeng; Wu, Guangming; Fu, Pingqing; Zhang, Yanlin; Bhattarai, Hemraj; Cong, Zhiyuan
Abstract: Biomass burning (BB) is one of the largest sources of carbonaceous aerosols with adverse impacts on air quality, visibility, health and climate. BB emits a few specific aromatic acids ( p -hydroxybenzoic, vanillic, syringic and dehydroabietic acids) which have been widely used as key indicators for source identification of BB-derived carbonaceous aerosols in various environmental matrices. In addition, measurement of p -hydroxybenzoic and vanillic acids in snow and ice cores have revealed the historical records of the fire emissions. Despite their uniqueness and importance as tracers, our current understanding of analytical methods, concentrations, diagnostic ratios and degradation processes are rather limited and scattered in literature. In this review paper, firstly we have summarized the most established methods and protocols for the measurement of these aromatic acids in aerosols and ice cores. Secondly, we have highlighted the geographical variability in the abundances of these acids, their diagnostic ratios and degradation processes in the environments. The review of the existing data indicates that the concentrations of aromatic acids in aerosols vary greatly with locations worldwide, typically more abundant in urban atmosphere where biomass fuels are commonly used for residential heating and/or cooking purposes. In contrast, their concentrations are lowest in the polar regions which are avoid of localized emissions and largely influenced by long-range transport. The diagnostic ratios among aromatic acids can be used as good indicators for the relative amounts and types of biomass (e.g. hardwood, softwood and herbaceous plants) as well as photochemical oxidation processes. Although studies suggest that the degradation processes of the aromatic acids may be controlled by light, pH and hygroscopicity, a more careful investigation, including closed chamber studies, is highly appreciated. Graphical abstract: Schematic overview on the sources, transport, and deposition of biomass burning emissions. Image 1 Highlights: The analytical methods to quantify aromatic acids as BB tracer are summarized. Abundances of the aromatic acids as BB tracer in different environments are discussed. Degradation and hygroscopic properties have not been clarified up to now. Perspectives involving measurement and field observation are recommended. Abstract : Current research trends on aromatic acids as biomass burning tracers were comprehensively reviewed.